International Service Learning: Occupational Therapists' Perceptions of Their Experiences in Guatemala - Jason C. Lawson; Myrna R. Olson (Scholarworks @ WMU, 2017)
The U.S. is fast becoming more culturally diverse, creating a greater need for entry-level occupational therapists to be culturally competent. In order to increase students' cultural competence, there is a growing support for international service learning (ISL). The purpose of this qualitative research study was to explore the perspectives of occupational therapy practitioners who engaged in ISL as occupational therapy students. Interviews were conducted with nine practicing occupational therapists, all of whom graduated from the same occupational therapy program in the U.S. and participated in an ISL experience in Guatemala. Phenomenological methods were used to analyze the transcribed interviews for codes, categories, and themes. The three themes that emerged were: Participants reported encountering many new experiences that led to experiencing a variety of emotions, their experiences in the Guatemalan culture further contributed to a deeper level of understanding about culture, and all of the participants reported that their ISL experiences allowed them to practice occupational therapy skills and interventions with limited resources, which facilitated creativity and resourcefulness. The findings of this study support that completing ISL as students contributes to occupational therapists' personal and professional lives and offers a glimpse of potential long-term effects of completing an ISL experience.